Rheumatoid arthritis is getting less frequent—results of a nationwide population-based cohort study - Abhishek, Abhishek; Doherty, Michael; Kuo, Chang-Fu; Mallen, Christian D.; Zhang, Weiya; Grainge, Matthew J. (Oxford University Press, 2017)
Objectives: The objectives of this study were to examine changes in incidence and prevalence of RA between 1990 and 2014, and to explore if there is any geographic variation in incidence and prevalence of RA in the UK Methods: Design Prospective cohort study Setting Primary care Participants People contributing acceptable data to Clinical Practice Research Datalink (CPRD) between 01/01/1990 and 31/12/2014 were included. Read codes were used to identify RA cases ≥18 years in age. Outcomes Prevalence and incidence rates for each year standardised to the 2014 population. Region specific incidence and prevalence of RA for the year 2014 standardized to the overall population. Results: The incidence and prevalence of RA was 3.81 per 10,000 person-years and 0.67% respectively in 2014. The annual incidence of RA reduced by -1.6%(-0.8% to - 2.5%) between 1990 and 2014, with significant joinpoints at 1994 and 2002. The prevalence of RA increased by 3.7%(3.2% to 4.1%)/year from 1990 to 2005; and reduced by -1.1%(-2.0% to -0.2%)/year between 2005 and 2014. There were significant differences in the occurrence of RA throughout different regions of the UK, with highest incidence in East Midlands, Yorkshire and Humber; and highest prevalence in North East, and Yorkshire and Humber. Conclusion: The incidence of RA is decreasing, with a reduction in prevalence in recent years. There is significant geographic variation in occurrence of RA in UK. Further research is required to identify the reasons underlying this phenomenon so that public-health interventions can be designed to further reduce the incidence of RA.